Delayed diagnosis of intrapartum uterine rupture – maternal and neonatal consequences. (4th March 2021) - Rottenstreich, Misgav; Rotem, Reut; Hirsch, Ayala; Farkash, Rivka; Rottenstreich, Amihai; Samueloff, Arnon; Sela, Hen Y.
Abstract: Objective: To assess the maternal and neonatal outcomes following delayed diagnosis of uterine rupture (diagnosis during the early postpartum period) in comparison to women with an intrapartum diagnosis of uterine rupture. Methods: Retrospective study of electronic medical records (EMR) from 2005 to 2018 in a single large academic tertiary care. Demographic, obstetric and maternal characteristics and outcomes were retrieved and compared. Univariate, followed by multivariate analyses were applied to evaluate the association between maternal and neonatal outcomes. Only complete uterine ruptures were included. The primary outcome of this study was defined as hysterectomy rates. Secondary outcomes were maternal and neonatal morbidity parameters. Results: During the study period, 143 parturients with uterine rupture were identified from 174, 189 deliveries (0.08%). Of these, 29 (20.3%) had delayed diagnosis with a median time from delivery to the operation of 4.5 hours (IQR 0.83–28 hours). Factors that were identified as independent risk factors for delayed diagnosis: an unscarred uterus (aOR 27.0, 95% CI 6.58–111.1), epidural analgesia during labor (aOR 7.9, 95% CI 2.32–27.05) and grand-multiparity (aOR 4.6, 95% CI 1.40–14.99). Maternal outcomes demonstrated that parturients with a delayed diagnosis had significantly higher rates of blood transfusions, puerperal fever, and hysterectomy ( p <.001 for all). In a multivariate model, the delayed diagnosis was found to be independently associated with hysterectomy (aOR 4.90, 95% CI 1.28–19.40). There were no differences regarding to neonatal outcomes. Conclusion: Parturients with delayed diagnosis of uterine rupture have unique characteristics and poorer maternal outcomes. It is possible that awareness of this population will enable earlier diagnosis and may help improve outcomes.